Interpreting human behavior from depositional rates and combustion features through the study of sedimentary microfacies at site Pinnacle Point 5-6, South Africa. Issue 85 (August 2015) - Karkanas, Panagiotis; Brown, Kyle S.; Fisher, Erich C.; Jacobs, Zenobia; Marean, Curtis W.
Abstract: Using fine and coarse resolution geoarchaeological studies at the Middle Stone Age site of PP5-6 at Pinnacle Point, Mossel Bay, South Africa, we discovered different patterns of anthropogenic input and changes in behavior through time. Through the microfacies approach, we documented the various geogenic and anthropogenic processes that formed the deposits of the site. By deciphering large scale rate differences in the production of these microfacies we estimated anthropogenic input rates and therefore gained understanding of occupational duration and intensity. The PP5-6 sediments document occupations characterized by small groups and short visits during Marine Isotope Stage (MIS) 5. This part of the sequence is characterized by numerous single (and mostly intact) hearth structures in a roofspall-rich matrix. During this time the sea was very close to the site and the people were focused on exploiting the rocky shores. With the advent of the glacial conditions of MIS4, the occupation of the site became much more intense. The occurrence of thick palimpsests of burnt remains, sometimes disturbed by small-scale sedimentary gravity processes, supports this conclusion. As sea level dropped and the coastline retreated, the geogenic input shifted to predominately aeolian sediments, implying an exposed shelf probably associated with a rich but more distant coastal environment. The occupants of PP5-6 turned their preference to silcrete as a raw material and they began to make microlithic stone tools. Since sites dating to MIS4 are abundant in the Cape, we suggest that populations during MIS4 responded to glacial conditions with either demographic stability or growth as well as technological change.